The personification of hospitality (Ḍiyāfah) in community development and its influence on social solidarity (Takāful Ijtimāʿī) through the eyes of the Prophetic Tradition (Sunnah) - Mohamed, Ahmad Hassan; Akbar, Mohamed Aslam; Abd. Aziz, Hassanuddeen (IIUM Press, International Islamic University Malaysia, 2020)
This paper tends to the subject of hospitality (ḍiyāfah) and elucidates its social standing and coupled terms by outlining the personification of hospitality in community development through the eyes of the Prophetic Tradition (Sunnah). The research clarifies the essential components of hospitality, with a specific spotlight on the association of human rights and the development of spirituality in different kinds of hospitality that were in practice during the early Muslims' period. The study features the influence of hospitality on social solidarity system (al-takāful al-ijtimāʿ) as it tends to the essential components related to the act of endowment (awqāf), the occasions of sacrificing animals (aḍāḥī), and the wedding banquets (ʿurūs). Lastly, the paper emphasizes that meaningful hospitality bears a significant impact on community development of society, and safeguarding human rights along with the spiritual progress promote education and encourage the growth of knowledge since ḍiyāfah is a gift which raises the humanity to achieve the divine guidance from God.